THE INFLUENCE OF EMOTIONAL INTELLIGENCE, TRUST, TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE TOWARD DECISION MAKING OF SENIOR MANAGER AT ISO 9000 CERTIFIED COMPANIES IN JABODETABEK AREA - Rachman Sjarief, Rachman Sjarief (Fakultas Ekonomi UM Metro, 1978)
ABSTRAK